AN ANALYSIS OF WOMEN REPRESENTATION IN “BLACK WIDOW” FILM BY CATE SHORTLAND: (A FEMINISM STUDY) - Utami, Sheila Geneviene; Widyahening, Ch. Evy Tri (ENGLISH RESEARCH JOURNAL, 2024)
This research was aimed to analyze the women representation shown in the film as represented by Natasha Romanoff in Black Widow film.                  This research was conducted at Slamet Riyadi University Library in 2024. To analyze the problem formulation, the researcher used a feminist approach. The researcher used feminism and impact role of women as race or ethnicity, and sexuality theories. In conducting the study, the researcher used method Miles and Huberman in analysis of qualitative data. The primary data is the Black Widow film written and directed by Cate Shortland. Secondary data is article, journal, book, and other previous research linked that could support the primary data.                  The findings of this research indicate that women represntation that show in Natasha Romanoff throughout the film. Natasha's concept of race, ethnicity, and sexuality is based on her Russian background, and Natasha’s as women representaion associated with Russian women. The part also touched on cultural stereotypes of Russian Women. Natasha embodies Russian traits, as seen in Natasha's actions and behavior throughout the film.                  It can be concluded that Natasha has an amazing women representation. Natasha emerges as a complex character who navigates her past traumas and current challenges with courage, compassion, and determination. Natasha can prove that woman offers a nuanced exploration of gender dynamics, empowerment, and resilience, providing a refreshing perspective on women representation. Keywords : Black Widow, Feminism, Gender Equality, Film, and Women Representation.